Identifying the Role of Cognitive Ability in Explaining the Level of and Change in the Return to Schooling - Heckman, James; Vytlacil, Edward (The Review of Economics and Statistics, 2001)
This paper considers two problems that arise in determining the role of cognitive ability in explaining the level of and change in the rate of return to schooling. The first problem is that ability and schooling are so strongly dependent that it is not possible, over a wide range of variation in schooling and ability, to independently vary these two variables and estimate their separate impacts. The second problem is that the structure of panel data makes it difficult to identify main age and time effects or to isolate crucial education-ability-time interactions which are needed to assess the role of ability in explaining the rise in the return to education.